Impact of workplace environment on employee performance: mediating role of employee health - Hafeez, Iqra; Yingjun, Zhu; Hafeez, Saba; Mansoor, Rafiq; Rehman, Khaliq Ur (Business, Management and Economics Engineering, 2019)
Purpose – Purpose of current study is to explore, impact of workplace environment i.e Physical Environmental Factors and Behavioral Environmental Factors on employee productivity (EP) through mediating role of employee health (EH). Research methodology – This study adopted questionnaire survey method and data was collected from 250 employees working in software houses in Pakistan. Data has been analysed using SPSS and AMOS software. Reliability and correlation analysis was performed by using SPSS while; path analysis was performed using AMOS. Findings – Results revealed that one unit variance in PEF incorporates 35% change in EH, 33% change in EH is caused by one unit increase in BEF and one unit increase in EH leads to 80% increase in EP. Physical and Behavioural Environmental Factors are positively affecting EH and EH is positivity affecting EP. Results of the study revealed that: employee health is mediating the relationship between workplace environment factors and employee performance. Research limitations – We used working Environment factors to determine employee health; future studies can consider compensation practices, insurance plans and health benefits by the organisation, a large sample or increased number of mediating variables can be used. The current study has adopted cross-sectional design while future studies can consider longitudinal design. Practical implications – Organisations must maintain a better environment in order to enhance employee productivity as, employee performance and workplace environment have direct and positive relationship, employees productivity and physical as well as behavioural environment are linked through employee health.